Surficial sediments of the Paraná Inner Continental Shelf, Southern Brazil - Sielski, Luiz Henrique; Angulo, Rodolfo José; Souza, Maria Cristina de; Veiga, Fernando Alvim (Quaternary and Environmental Geosciences, 2017)
This study examines surficial sediment distribution patterns, slope and morphological characteristics of the Paraná inner continental shelf. Paraná inner continental shelf is located on the southern Brazilian continental shelf, a wide and low gradient shelf, in the vicinity of two large unfilled estuaries and the Serra do Mar mountain range. It is characterized as a wave/storm dominated continental shelf with microtidal, semidiurnal regime and a small supply of recent continental sediments. We analyzed grain-size parameters and sediment composition of 875 grab samples and investigated the inner continental shelf morphology and slope through a digital bathymetric model built from regional nautical charts. We combined and evaluated the characteristics of grain-size curves, the spatial distribution of sediments, and the morphology and slope of the inner continental shelf to identify different sedimentary facies. Sediment distribution patterns change from the coast seaward and between three defined sectors along the coastline: south, central and north inner continental shelf. This variation seems to be related to recent sediment sources and to the presence of deposits from ancient coastal plain and inner continental shelf environments formed before the last Holocene sea-level highstand. Sediments with mean diameter of fine to very fine sands prevail at all depths. Deposits of sediments with mean diameter of silt and medium to coarse sands are significant in particular areas, generally associated with steep slopes, troughs, and sand ridges. Possible causes of sedimentary patchiness are the outcropping of medium to coarse sand and the supply of recent estuarine muddy sediments provided by large estuarine complexes to the Paraná inner continental shelf. The results obtained contribute to the knowledge about the sediment dynamics of Paraná inner continental shelf.